Religious experience as a starting point in the study of the anthropology of religion, or how to let go of the body in the rituals of others (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
Through a narrative of ritual participation, and a reflexivity exercise, I will explore categories such as “religious experience”, the role of the body, and the exercise of loosening the body, in order to discuss situationally some of the ways anthropology studies religion. Through this, I am looking to answer to the question of how the study of religion and the contact with different rituals affects my own anthropological work.
Keywords: religious experience; anthropology of religion; body; reflexivity